The Impact of Mobile Payments on the Financial Management Efficiency of Small and Medium-Sized Enterprises - Li, Qing (International Journal of Interactive Mobile Technologies (iJIM), 2024)
In recent years, mobile payment technology has rapidly developed and gradually become an integral part of daily economic activities, particularly within small and medium-sized enterprises (SMEs). The widespread adoption of mobile payments has significantly transformed financial management and operational models in SMEs. As vital drivers of economic growth, the financial management efficiency of SMEs is crucial to their survival and development. The extensive application of mobile payments not only facilitates daily transactions but also provides additional data and information support, potentially enhancing financial management efficiency. However, although numerous studies focus on the impact of mobile payments on business operations, there is a gap in the specific examination of their effect on the financial management efficiency of SMEs. Existing research predominantly addresses the impact of mobile payments on the overall market, lacking detailed analysis targeting SMEs. Furthermore, research methodologies often overlook the heterogeneity of user behavior on mobile payment platforms, failing to comprehensively reflect the differential impact on various types of enterprises. This study explores how user utility, user scale, platform profit, and equilibrium price affect the financial management efficiency of SMEs by constructing a theoretical model. It consists of two parts: initially defining financial management efficiency in SMEs and analyzing its influencing factors to update their financial management models. Subsequently, it examines the impact of mobile payment platforms on these factors through empirical analysis and model derivation. The findings demonstrate that mobile payment technology significantly enhances the financial management efficiency of SMEs, offering useful insights for business management and policy-making.